Variation in vegetation cover affect the herpetofauna assembly composition at the Serra Azul, eastern Amazon - da Silva Fróis, Raul de Paula; Celerino de Carvalho, Joyce; Hernández Ruz, Emil José (Revista de Biologia Neotropical / Journal of Neotropical Biology, 2018)
The impacts of landscape alteration on herpetofauna assemblages can have negative consequences in the fauna composition, related to changes in the distribution and species diversity. Inthis study was evaluated the effect of vegetation in the composition of the herpetofauna communityin a fragmented landscape of eastern Amazon, specify in the Serra Azul region, located in the Lower Amazon, municipality of Monte Alegre on Pará State. We used two sampling methods: time-constrainedsearches and pitfall traps with drift fences. Sampling occurred in four localities with different land usehistory and vegetation cover. The sampling occurred during the rainy and dry seasons between the years2013-2014, twice on begin rainy and once on begin dry, totaling a sampling effort of 120 hours-catcherand traps 1.912 hours-bucket. We record 23 species of anurans and 27 species of reptiles (12 lizards, 12 snakes, two turtles and one alligator). The species accumulation curve tended to stabilize. The richness of species estimated in this study was 71 (± 4.74). The richness of the community was higher in weir localities and crops area and lower in forest and primary forest edge localities.